Edukasi Hilirisasi Kelor untuk Mendorong Agropreneurship Berbasis Potensi Lokal - Utami, Sri Sari; Widowati , Rahayu (Rahmatan Lil 'Alamin Journal of Community Services, 2026)
Moringa (Moringa oleifera) is a multipurpose plant with high potential as a functional food and economic commodity; however, its utilization at the village level remains limited. This community service activity aimed to enhance community knowledge, awareness, and motivation in utilizing moringa as a basis for local-based agropreneurship. The program was conducted in Wukirsari Village, Cangkringan District, Sleman Regency, Special Region of Yogyakarta, involving representatives of women farmer groups, PKK members, and village officials. An educational approach was applied through counseling sessions covering nutritional and health benefits of moringa, its economic potential, downstream processing opportunities, and basic entrepreneurship concepts. Data were collected through discussions, question-and-answer sessions, and observation. The results indicate that approximately 90% of participants had consumed moringa in daily life, but its utilization remained limited to traditional preparations. The activity improved participants’ understanding of value-added processing and business opportunities. High enthusiasm and participation reflected social readiness to develop moringa-based agropreneurship. This program is expected to serve as an initial step toward promoting downstream processing, increasing product value, and strengthening sustainable community-based economic development.